A Study on the Effect of UWB Interference on Downlink UMTS System - Al-Adwany, Maan A. S.; Najim, Esra’a H.; Ali, Ala’a B.; Younis, Amina M. (Iraqi Journal for Electrical and Electronic Engineering, 2010)
In this paper, we evaluate the performance of UMTS (Universal Mobile Telecommunication System) downlink system in vicinity of UWB system. The study is achieved via simulating a scenario of a building which is located within UMTS cell borders and utilizes from both UMTS and UWB appliances. The simulation results show that the UMTS system is considerably affected by the UWB interference. However, in order to battle this interference and achieve reasonable BER (Bit Error Rate) of 10 -4 , we found that it is very necessary to carefully raise the UMTS base station transmitted power against that of UWB interferer. So, the minimum requirements for UMTS system to overcome UWB interference are stated in this work.